Navigating Virtual Bonds : Human-AI Friendship Dynamics through the Lens of Uncertainty Reduction Theory - Maria Vina Elmaresa (Universitas Multimedia Nusantara, 2024)
This research examines the dynamics of human interaction and artificial intelligence (AI) through chatbots such as ChatGPT and character.ai. Data was collected using a qualitative approach and single case study methodology using two informants' in-depth interviews. Data analysis was carried out using pattern matching, emphasizing the axioms of uncertainty reduction theory. The research results show a decrease in uncertainty and skepticism towards AI through increased verbal communication and information seeking. However, this research also reveals limitations in applying uncertainty reduction theory to human and AI interactions. From the research, there is a possibility of a shift in interaction from humans to AI to seek emotional support, replacing the traditional role of humans. This research contributes to understanding the development of the relationship between humans and AI, namely how humans assign social roles to AI. Additionally, it adds to the growing body of work that views AI as more than just a medium but a communicator.